Monitoring Environmental Conditions in Airports with Wireless Sensor Networks - Nayra Rodríguez-Pérez; Pino Caballero-Gil; Josué Toledo-Castro; Iván Santos-González; Candelaria Hernández-Goya (Proceedings, 2018)
In recent decades, the environment has suffered the negative consequences of industrial development and overexploitation, and the effect of growing population. There are many areas and sectors where actions can be taken to minimize negative environmental impacts. Despite the current technological advances in society, there is a pending debt to nature, environment and care of air quality. This paper presents a system based on Wireless Sensor Networks, whose objective is to monitor environmental conditions in airport environments. Since the proposed system allows managing notifications and alerts when dangerous conditions are detected, it can also be considered a procedure to protect critical infrastructures in general. Due to the importance of security requirements in these facilities, the system includes several cryptographic measures to provide robust authentication and encryption of information.